Cover Feature: A Novel Sterically Bulky Hole Transporter to Remarkably Improve the Lifetime of Thermally Activated Delayed Fluorescent OLEDs at High Brightness (Chem. Eur. J. 18/2018). Issue 18 (5th February 2018) - Kamata, Takahiro; Sasabe, Hisahiro; Igarashi, Masahiro; Kido, Junji
Abstract : A hexaphenylbenzene derivative hole‐transporter significantly enhances the lifetime of organic light‐emitting devices (OLEDs) based on thermally activated delayed fluorescence (TADF) at high brightness. A green TADF OLED simultaneously achieves a high external quantum efficiency of over 20 %, a high power efficiency of 54 lm W −1, and operation lifetime at 50 % of approximately 10 000 h at 1000 nit. This result promises a bright future for TADF OLED. More information can be found in the Full Paper by H. Sasabe, J. Kido et al. on page 4590 .